2010
DOI: 10.1093/eurjhf/hfq037
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tissue inhibitor of matrix metalloproteinase‐1 (TIMP‐1): an independent predictor of poor response to cardiac resynchronization therapy

Abstract: AimsMatrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) play a role in left ventricular structural remodelling. The aim of our study was to analyse MMP-2 and TIMP-1 levels as predictors of poor response to cardiac resynchronization therapy (CRT).Methods and resultsA cohort of 42 CRT patients from our centre was prospectively evaluated at baseline and after 12-month follow-up. MMP-2 and TIMP-1 assays were performed prior to CRT implant. Cardiac resynchronization therapy responders were defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
3
21
0
2
Order By: Relevance
“…A recent work has suggested that a significant decrease in MMP-9 levels correlates with CRT-associated RR* over a 6-month follow-up period [111]. Furthermore, higher TIMP-1 levels have been shown to be an independent predictor of nonresponse to CRT [112]. Increased collagen production resulting in excessive fibrosis can exert a deleterious effect on ventricular function.…”
Section: Biomarkers In Cardiac Resynchronization Therapymentioning
confidence: 99%
“…A recent work has suggested that a significant decrease in MMP-9 levels correlates with CRT-associated RR* over a 6-month follow-up period [111]. Furthermore, higher TIMP-1 levels have been shown to be an independent predictor of nonresponse to CRT [112]. Increased collagen production resulting in excessive fibrosis can exert a deleterious effect on ventricular function.…”
Section: Biomarkers In Cardiac Resynchronization Therapymentioning
confidence: 99%
“…The PICP:CITP ratio was considered an index of the degree of coupling between the synthesis and degradation of collagen type I [7]. Serum levels of MMP-1, -2 -3, and -9, and TIMP-1 were analyzed using commercially available 2-site sandwich enzyme-linked immunosorbent assay (Quantikine R&D Systems, Minneapolis, Minnesota, USA) [8]. Intra-and inter-assay variations for determining MMPs and TIMP-1 were all b8%.…”
Section: Measurements Of Circulating Biomarkers Of Collagen Metabolismmentioning
confidence: 99%
“…Дисбаланс в системе цитокинов может приве-сти к ремоделированию миокарда вследствие активации матриксных металлопротеиназ (MMPs), вызывающих деградацию коллагена и ремоделирование экстрацел-люлярного кардиального матрикса (ЭКМ) [19], а также к развитию фиброза миокарда [20,21]. Известно влияние СРТ на процессы воспаления [22][23][24][25], ремоделирования экстрацеллюлярного кардиального матрикса (ЭКМ) [26][27][28], фиброобразования [29,30]. Однако влияние этих процессов на гендерную специфику ремоделирова-ния миокарда на фоне СРТ не изучено.…”
Section: Discussionunclassified
“…Имеются сведения о влиянии СРТ на активность систе-мы MMPs и их тканевых ингибиторов (TIMPs), играю-щих ключевую роль в ремоделировании ЭКМ [26][27][28]. Модернизация ЭКМ по сути является адаптивным про-цессом, ведущим к изменению растяжимости миокарда, сохранению геометрической формы сердца или формиро-ванию новой конструкции камер сердца.…”
Section: Discussionunclassified